A stress MRI of the shoulder for evaluation of ligamentous stabilizers in acute and chronic acromioclavicular joint instabilities. Issue 6 (16th November 2012) - Izadpanah, Kaywan; Winterer, Jan; Vicari, Marco; Jaeger, Martin; Maier, Dirk; Eisebraun, Leonie; Ute Will, Jutta; Kotter, Elmar; Langer, Mathias; Südkamp, Norbert P.; Hennig, Jürgen; Weigel, Mathias
Abstract Purpose: To show the feasibility of a stress magnetic resonance imaging (MRI) as a new method for simultaneous evaluation of the morphology and the functional integrity of the acromioclavicular joint (ACJ) ligamentous stabilizers. Materials and Methods: MRI of four volunteers, 10 patients with acute, and six with chronic ACJ injuries was performed using a 0.25 T open MRI scanner. A 2D‐proton‐density and a 3D‐gradient‐echo sequence at rest and under 6.5 kg shoulder traction were performed. Comparative measurements of the coracoclavicular and the acromioclavicular distance were performed. Additionally, the conoid and trapezoid ligament lengths were measured with multiplanar reconstructions. Results: MRI at rest correctly identified tears of the coracoclavicular and the acromioclavicular ligaments in eight patients suffering acute ACJ injuries. Stress application helped to distinguish between partial and complete coracoclavicular ligament tears in two cases. Insufficiency of the ACJ ligaments was present in all acute and chronic ACJ injuries. Stress application in chronic ACJ ligaments revealed isolated insufficiency of the conoid ligament in three cases and of the trapezoid ligament in one case. Combined insufficiency was present in two cases. Conclusion: Stress MRI facilitates simultaneous acquisition of morphologic and functional information of the ACJ stabilizers. In acute ACJ injuries it helps to distinguish between partial and complete ligament tears. In chronic ACJ injuries it provides functional information of the ligament regrinds. J. Magn. Reson. Imaging 2013;37:1486–1492. © 2012 Wiley Periodicals, Inc.